Image-analysis based on seed phenomics in sesame - Prasad, R.; Mukherjee, K. K.; Gangopadhyay, G. (Plant Breeding and Seed Science, 2013)
The seed coat (testa) structure of twenty-three cultivated (Sesamum indicum L.) and six wild sesame (S. occidentale Regel & Heer., S. mulayanum Nair, S. prostratum Retz., S. radiatum Schumach. & Thonn., S. angustifolium (Oliv.) Engl. and S. schinzianum Asch) germplasm was analyzed from digital and Scanning Electron Microscopy (SEM) images with dedicated software using the descriptors for computer based seed image analysis to understand the diversity of seed morphometric traits, which later on can be extended to screen and evaluate improved genotypes of sesame. Seeds of wild sesame species could conveniently be distinguished from cultivated varieties based on shape and architectural analysis. Results indicated discrete ‘cut off’ values to identify definite shape and contour of seed for a desirable sesame genotype along with the conventional practice of selecting lighter colored testa.